Effectiveness of influenza vaccine in children in day-care centers of Sapporo - Mori, Mitsuru; Hasegawa, Junko; Showa, Satoko; Matsushima, Aiko; Ohnishi, Hirofumi; Yoto, Yuko; Tsutsumi, Hiroyuki (Pediatrics international, 2014)
Background We conducted a retrospective cohort study for evaluating the effectiveness of the trivalent inactivated influenza vaccine (TIV) among children aged 0–6 years in the 2011–2012 season in Sapporo City, Japan, because of scarce evidence. Methods From 10 day‐care centers in Sapporo City, Japan, 629 parents participated in the study. Each parent of the subjects described whether a subject received TIV once or twice in the 2011–2012 season, as well as the exact dates of receiving TIV from records in a maternal and child health handbook marked by a pediatrician. The incidence of influenza was defined as being affected with influenza as diagnosed by a pediatrician. Cox's proportional model was used for calculating a hazard ratio (HR) and its 95% confidence interval (95%CI) of TIV on an influenza incidence. Results After adjusting potential confounding variables, such as the day‐care center, presence of comorbidity, size of household, number of siblings, and number of smokers in the home in addition to the age and sex of the child, HR was significantly reduced in the subjects aged 1 year (HR = 0.22, 95%CI 0.09–0.54) as well as in the total subjects (HR = 0.72, 95%CI 0.52–0.99). Consequently, the effectiveness of TIV was calculated as 78% for the subjects aged 1 year and 28% for the total subjects. Conclusion Our study suggests that TIV is effective, especially in subjects aged 1 year. Further studies are necessary in different seasons, places, and populations to clarify the effectiveness of the influenza vaccine in children.